Fostering Students’ Speaking Ability Through Storytelling Technique At The Tenth Grade Of SMA Negeri 13 Maluku Barat Daya - Anidlah, Apriliani; Meyer, Fredy; Tiwery, Yulina (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2023)
The objective of this study was to foster the speaking abilities of the tenth grader students at SMA NEGERI 13 MBD, which amounted to 22 students. This research used Classroom Action Research. The steps were preliminary study, planning, implementation, evaluation and reflection. The data were collected through pre-test and post-test, teacher observation and the students’ feedback through questionnaire. This study occurred over two cycles and consisted of nine meetings. The data showed that the first cycle was not successful because it only achieved 22. 27 % therefore it continued to second cycle and there was an increase to 86.3%. Based on the outcomes, the storytelling technique had a significant positive impact on students’ speaking proficiency especially in four main aspects, performance, pronunciation, grammar and vocabulary. Through storytelling technique, the students were able to deliver a story in an innovative and imaginative way, giving them the courage to express themselves in front of the class.